2022
DOI: 10.33687/10.33687/ijae.010.01.4195
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional attributes of carps fed varying protein levels in supplemental diets under pond polyculture conditions

Abstract: This study examined the effects of six iso-caloric supplemental diets differing in amounts of protein (22, 24, 26, 28, 30, and 32%) on the fillet composition of rohu (Labeo rohita), catla (Catla catla), mrigal (Cirrhina mrigala), grass carp (Ctenopharyngodon idella) and silver carp (Hypophthalmichthys molitrix) raised in ponds containing natural feed. Control treatment with no supplemental feeding was also included. Mean muscle protein concentrations were significantly lower in fish from control ponds compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The elevation in DFC, TFC, DPC, TPC, FFR, and PPV in fish obtained diets containing 28% protein (T2) compared to the fish feeds (T1: 30%, T3: 26%, and T4: 35% of protein) can be attributed to several factors supported by existing research. The observed augmentation in feed efficiency in fish-fed diets with 28% protein is consistent with research on the optimization of protein in supplementary feeds for pond-raised cyprinids, which showed that net fish yield is enhanced as the level of digestible protein in the supplementary diets increased and plateaued at 28% dietary protein level (Zeb & Javed, 2018). Additionally, a study on the Far Eastern catfish (Silurus lotus) showed that DFC and DPC were significantly affected by dietary protein levels, with the final mean weight improved with increasing dietary protein levels, indicating a positive correlation between protein levels and feed consumption (Kim et al, 2012).…”
Section: T4 (35%) Initialsupporting
confidence: 86%
“…The elevation in DFC, TFC, DPC, TPC, FFR, and PPV in fish obtained diets containing 28% protein (T2) compared to the fish feeds (T1: 30%, T3: 26%, and T4: 35% of protein) can be attributed to several factors supported by existing research. The observed augmentation in feed efficiency in fish-fed diets with 28% protein is consistent with research on the optimization of protein in supplementary feeds for pond-raised cyprinids, which showed that net fish yield is enhanced as the level of digestible protein in the supplementary diets increased and plateaued at 28% dietary protein level (Zeb & Javed, 2018). Additionally, a study on the Far Eastern catfish (Silurus lotus) showed that DFC and DPC were significantly affected by dietary protein levels, with the final mean weight improved with increasing dietary protein levels, indicating a positive correlation between protein levels and feed consumption (Kim et al, 2012).…”
Section: T4 (35%) Initialsupporting
confidence: 86%